Early Unplanned Reoperation After Glioma Craniotomy: Incidence, Predictor and Process Improvement - Zhang, Yu; Ji, Peigang; Wang, Shoujie; Qin, Huaizhou; Cai, Qing (Frontiers in Oncology, 2022)
Objective To evaluate the rate of, reasons for, and predictors of unplanned reoperation after craniotomy for glioma in a single-institution consecutive series. Methods Patients who underwent glioma resection at our hospital from 2015 to 2021 were included (n=1563). Multivariate logistic regression was used to examine the predictors of early unplanned cranial reoperation. The predictors that were screened included patient age, sex, tumor properties, blood loss, blood pressure and antiplatelets drugs usage. Results A total of 3.6% (56/1563) of the patients underwent an early unplanned reoperation after craniotomy for glioma. The reasons for early unplanned reoperation were brain edema (48.2%), cerebral infarction (33.9%) and hemorrhage (17.9%). The predictors of early unplanned reoperation were WHO grade III-IV, peritumoral edema ≥1 cm, subtotal resection, arterial/venous involvement and elevation in blood pressure ≥50 mmHg. Conclusions Glioma properties and blood pressure management are decisive predictors of early unplanned reoperation for glioma resection. The authors provide a nuanced discussion regarding early unplanned reoperations and perioperative process improvement as a quality indicator for glioma patient populations.